Effect of patient-specific scapular morphology on the glenohumeral joint force and shoulder muscle force equilibrium: a study of rotator cuff tear and osteoarthritis patients - Oswald, Alexandra; Menze, Johanna; Hess, Hanspeter; Jacxsens, Matthijs; Rojas, J. Tomas; Lädermann, Alexandre; Schär, Michael; Ferguson, Stephen J.; Zumstein, Matthias A.; Gerber, Kate (Frontiers in Bioengineering and Biotechnology, 2024)
Osteoarthritis (OA) and rotator cuff tear (RCT) pathologies have distinct scapular morphologies that impact disease progression. Previous studies examined the correlation between scapular morphology and glenohumeral joint biomechanics through critical shoulder angle (CSA) variations. In abduction, higher CSAs, common in RCT patients, increase vertical shear force and rotator cuff activation while lower CSAs, common in OA patients are associated with higher compressive forces. However, the impact of the complete patient-specific scapular morphology remains unexplored due to challenges in establishing personalized models. In this study, CT data of 48 OA patients and 55 RCT patients was collected. An automated pipeline customized the AnyBody™ model with patient-specific scapular morphology and glenohumeral joint geometry. Biomechanical simulations calculated glenohumeral joint forces and instability ratios (shear to compressive forces). Moment arms and torques of rotator cuff and deltoid muscles were analyzed for each patient-specific geometry. This study confirms increased instability ratio on the glenohumeral joint in RCT patients during abduction (mean maximum 32.80% higher than OA), while OA patients exhibit higher vertical instability ratio in flexion (mean maximum 24.53% higher than RCT) due to increased inferior vertical shear force. This study further shows lower total joint force in OA patients compared to RCT patients (mean maximum total force for the RCT group 11.86% greater than for the OA group), attributed to mechanically advantageous muscle moment arms. The findings highlight the significant impact of glenohumeral joint center positioning on muscle moment arms and the total force generated. We propose RCT pathomechanism relates to force magnitude, while OA pathomechanism associates with shear-to-compressive loading ratio. Overall, this research contributes to understanding of the impact of the individual complete 3D scapular morphology on shoulder biomechanics.